Phenotypic and Molecular Characterization of β-Lactamases among Enterobacterial Uropathogens in Southeastern Nigeria. (25th February 2020) - Ugwu, M. C.; Shariff, M.; Nnajide, C.M.; Beri, K; Okezie, U. M.; Iroha, I. R.; Esimone, C. O.
Abstract : Little is known about the molecular basis of antibiotic resistance among uropathogens in Southeast Nigeria. The aim of the study was to characterize enterobacterial uropathogens with respect to drug resistance. One hundred (100) enterobacterial uropathogens were studied. Their antibiotic susceptibility patterns were evaluated using disk diffusion, screened, and confirmed phenotypically for the presence of β -lactamases: ESBL, AmpC, carbapenemase, and MBLs. Screen positives were further tested for various β -lactamase genes by PCR. Our isolates showed variable resistance to most drugs tested. Out of the 58 ESBL screen positive E. coli, 35 were confirmed positive with PCR. The predominant ESBL gene was blaTEM while blaSPM was the most prevalent among MBL genes. Forty-six percentage of the screen positive Salmonella isolates coharbored blaTEM + SHV genes. Nine of the 10 ESBL screen positive K. pneumoniae were phenotypically and PCR positive. Three isolates of K. pneumoniae were positive for MBL genes. All the 10 C. freundii were positive for ESBL genes. The study showed high prevalence of drug-resistant genes among the enterobacterial uropathogens. Majority of the uropathogens harbored >1 antibiotic-resistant gene, and the most predominant gene was ESBL (blaTEM ) followed by the MBL (SPM) gene.